High inclusion rate of wet corngluten feed on performance oflate-lactation holstein cows:preliminary results - D.J. Rezac; K.N. Grigsby; Barry J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2008)
A novel diet formulation strategy incorporating wet corn gluten feed at 47% of diet dry matter was evaluated in late-lactation cows. Diets were formulated for similar protein and energy concentrations with dramatic differences in forage sources. Milk fat and protein concentrations increased with the high wet corn gluten feed inclusion rate, and this diet tended to increase milk fat yield. The preliminary work indicates that very low cost rations incorporating wet corn gluten feed may be formulated to maintain milk production, at least in late-lactation cows.; Dairy Day, 2008, Kansas State University, Manhattan, KS, 2008; Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy Day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-134-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1002; Inclusion rate; Wet corn; Gluten feed; Performance; Lactation; Holstein